A MODEL FOR IMPROVING THE ERROR-CORRECTING COMPETENCE OF FUTURE GERMAN LANGUAGE TEACHERS (Scientific journal of the Fergana State University, 2025)
The article discusses the model for improving students' error-correcting competence in future German language teachers. Effective correction of students' mistakes and their elimination, taking into account the individual characteristics of the language learner, to achieve efficiency based on the development of skills in the work to be done so that the correction process does not cause demotivation of language learners are analyzed.